Examining nursing students' wellness and resilience: An exploratory study. (February 2021) - Spurr, Shelley; Walker, Keith; Squires, Vicki; Redl, Nicole
Abstract: Undergraduate nursing students report high levels of stress which can negatively impact their overall wellness, and their academic and clinical performance. Despite this knowledge, there are few studies that have examined the well-being of nursing students and their ability to demonstrate resilience. Therefore, the purpose of this exploratory study was to examine resilience and wellness, together with the key factors that promote a well-being in nursing students from mid-western Canadian university. The sample of 196 undergraduate nursing students completed an online Nursing Well-being and Resilience Survey . Findings indicated that most nursing students had good health; however, many presented with anxiety and/or depression and a decreased sense of wellness in the physical, spiritual, and emotional domain. Other significant findings included participants >26 years old having lower burnout scores, higher ego-resilience and well-being scores compared to students ages 20 to 25; and, 2) there were differences between campus locations in terms of Professional Quality of life (compassion satisfaction, burnout, and traumatic stress) and sense of well-being. Understanding how resilience and wellness are influenced throughout the nursing program is a first step in developing targeted wellness initiatives for different nursing student populations. Highlights: Students find undergraduate nursing education stressful. Most nursing students had good health; however, many presented with anxiety and/or depression. Many indicated a lower sense of wellness in the physical, emotional and spiritual dimensions. Participants >26 years old have lower burnout scores, higher ego-resilience and well-being scores. Professional Quality of Life and sense of wellbeing varies between primary location and distributed learning sites.